Environment-Friendly Construction Materials - Wu, Shaopeng (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Construction materials are the most widely used materials for civil infrastructure in our daily lives. However, from an environmental point of view, they consume a huge amount of natural resources and generate the majority of greenhouse gasses. Therefore, many new and novel technologies for designing environmentally friendly construction materials have been developed recently. This Special Issue, "Environment-Friendly Construction Materials", has been proposed and organized as a means to present recent developments in the field of construction materials. It covers a wide range of selected topics on construction materials.